A very inconvenient scandal [large type] - Mitchard, Jacquelyn (Thorndike Press large print top shelf., 2023)
"Stunned by her recently widowed father's reckless behavior, a young woman must learn to navigate a new world--where the people she should trust the most have become strangers she cannot trust at all. Frankie Attleboro returns home to Cape Cod with thrilling news. She's met the love of her life, and they're getting married with a baby on the way. That's the moment her father makes his own jas-dropping announcement: at sixty, he's getting married as well, to Frankie's best friend, Ariel, who is also pregnant, and due soon. As Frankie and Ariel struggle to adjust to their new relationship, Ariel's estranged mother, Carlotta, returns after a decade-long absence. She claims to be a changed woman, but is she really? And where has she been all these years? Frankie is suspicious, and as Carlotta's unpredictable behavior intensifies, Frankie must untangle the threads of the past to protect Ariel's future--and her own" --